1990
DOI: 10.1093/ije/19.1.164
|View full text |Cite
|
Sign up to set email alerts
|

How to Predict the Immune Status of Poliovirus Vaccinees? A Comparison of Virus Neutralization at a Very Low Serum Dilution versus ELISA in a Cohort of Infants

Abstract: A cohort of children from Gaza was observed from birth to the age of one year. Blood specimens were collected at birth, before and after poliovirus vaccination and at one year of age. Poliovirus immunity before and after vaccination was assessed by ELISA and virus neutralization (NT). Positive predictive values for ELISA were between 81.5% and 90.8%. However, ELISA revealed a high frequency of false negatives, and unacceptably low negative predictive values between 28.6% and 55.4%. The history of poliovirus im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The increased antibody response induced by CAF01 also correlated with an increased cellular response measured by multiplex cytokine analysis. Although the cellular immune response is not considered a direct correlate of protection for polio vaccines it may play an indirect role by supporting a memory B cell response [56,57]. Our analysis of anti-IPV T cell immunity revealed that CAF01 induced both a faster and stronger response against IPV.…”
Section: The Caf01 Induced Immune Response Against Ipvmentioning
confidence: 85%
“…The increased antibody response induced by CAF01 also correlated with an increased cellular response measured by multiplex cytokine analysis. Although the cellular immune response is not considered a direct correlate of protection for polio vaccines it may play an indirect role by supporting a memory B cell response [56,57]. Our analysis of anti-IPV T cell immunity revealed that CAF01 induced both a faster and stronger response against IPV.…”
Section: The Caf01 Induced Immune Response Against Ipvmentioning
confidence: 85%
“…28,42,50,51 Neutralizing antibody titer generally has been accepted as the correlate of protection for poliovirus vaccines and is used as the gold standard to determine effectiveness of poliovirus vaccination. 52,53 However, mucosal IgA responses have also been reported to be important for control of poliovirus infection. 41,54,55 Salivary and fecal IgA are considered to represent the common mucosal immune response (secretory IgA) that can prevent initial pathogen entry, while circulating IgA and IgG form a second line of defense, mediating elimination of pathogens that have breached the mucosal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular immune response is not considered a direct correlate of protection for polio vaccines it may play an indirect role by supporting a memory B cell response [35,36]. Our analysis of anti-IPV T cell immunity revealed that aluminium hydroxide induced both a faster and stronger response against IPV.…”
Section: The Aluminium Hydroxide Induced Immune Response Against Ipvmentioning
confidence: 82%